GAMBARAN STATUS GIZI PADA PASIEN HIPERTENSI LANSIA - Indri Adam; Indra Domili; Rahma Labatjo (JOURNAL HEALTH AND NUTRITIONS, 2019)
Hypertension is a disease that can affect anyone, whether young or old, whether rich or poor. Hypertension is one of the deadliest diseases in the world. As many as 1 billion people in the world or 1 in 4 adults suffer from this disease. It is even estimated that the number of people with hypertension will increase to 1.6 billion by 2025.This study aims to determine the description of the nutritional status of elderly hypertension in the working area of the North City Health Center.The type of research used in this study is a descriptive survey method, namely to obtain an overview of the nutritional status of elderly hypertensive patients. The research sample was 54 people. Data analysis using univariate analysis.Nutritional status of the hypertensive elderly in the North City Health Center Working Area with the category of normal nutritional status 16 people, 18 overweight people and the hypertensive elderly in the North City Health Center Working Area with blood pressure of 140-159 mmHg (Stage 1) as many as 23 people. or equivalent to 63.88%.Overview of the Nutritional Status of Elderly Hypertensive Patients In the North City Health Center Work Area the most with blood pressure of 140-159 mmHg or stage 1 hypertension. Most or 50% of 36 elderly hypertension patients have overweight nutritional status .Hipertensi merupakan suatu  penyakit yang bisa menyerang siapa saja, baik mudah maupun tua, entah orang kaya maupun miskin. Hipertensi merupakan salah satu penyakit paling mematikan di dunia. Sebanyak 1 miliar orang di dunia atau 1 dari 4 orang dewasa menderita penyakit ini. Bahkan diperkirakan jumlah penderita hipertensi akan meningkat menjadi 1,6 milyar menjelang tahun 2025.Penelitian ini bertujuan untuk Mengetahui gambaran status gizi hipertensi lansia di wilayah kerja Puskesmas Kota Utara.Jenis penelitian yang digunakan pada penelitian ini adalah metode survei deskriptif yaitu untuk memperoleh gambaran status gizi pasien hipertensi lansia. Sampel penelitian sebanyak 54 orang. Analisis data menggunakan analisis univariat. Status  gizi pada lansia hipertensi di Wilayah Kerja Puskesmas Kota Utara dengan kategori status gizi normal 16 orang, kelebihan berat badan 18 orang dan lansia yang hipertensi di Wilayah Kerja Puskesmas Kota Utara dengan tekanan darah 140-159 mmHg (Stadium 1) sebanyak 23 orang atau setara dengan 63,88%.Gambaran Status Gizi Pasien Hipertensi Lansia Di Wilayah   Kerja Puskesmas Kota Utara paling banyak dengan tekanan darah 140-159 mmHg atau hipertensi stadium 1. Sebagian besar atau 50% dari 36 orang pasien hipertensi lansia memiliki status gizi kelebihan berat badan